A modified movement screen for pre-elite youth athletes - Moore, N.; Kertesz, A.; Bird, S. P. (Journal of Australian Strength and Conditioning, 2012)
An emerging role of the strength and conditioning coach in athletic preparation is the application of movement screening assessment. Determining the athletes` movement strategy that not only incorporates the interplay between stability and mobility, but also the interactions between force production and force reduction may assist in program development. Movement screening is an effective assessment tool to examine such qualities and aims to identify movement limitations and/or dysfunction related to strength deficits, muscle imbalances and/or compensatory movement patterns. We have recently used a modified-4 movement screen for pre-elite youth athlete`s that is quick and easy to administer. The modified-4 movement screen consists of four movement patterns; (i) overhead squat; (ii) push up10; (iii) prone hold120; and (iv) tuck jump10. This article will briefly define the role of movement screening in strength and conditioning, and outline how to conduct the modified-4 movement screen as part of your athletic assessment.